Share repurchase announcements : an analysis of price movements of owner managed and non-owner managed companies. - Chang, Adeline Pei Li. (2008)
This report attempts to find out if investors’ perception of the credibility of share repurchase announcements is influenced by whether the stewards of the companies are also the owners. The findings, based on research done on U.S. listed companies, seem to suggest that there is a correlation between upward share price movement and the ownership structures of repurchasing companies.